ASSESSMENT OF ORAL HEALTH BEHAVIOR IN ADOLESCENTS WITH VARIOUS SOCIAL BACKGROUNDS - Alice Murariu; Doriana Agop Forna; Livia Bobu; Diana Oiță; Petruța Siminiuc; Sorana Roșu; Diana Zapodeanu; Elena Raluca Baciu (Romanian Society of Oral Rehabilitation, 2024)
The cross-sectional study was carried out in two high schools (one rural and the other one urban) with the aim of assessing the differences in oral health behavior between the two samples of teenagers. Materials and methods: An original questionnaire containing 17 questions was used in the study, which was completed by 251 adolescents aged between 15-17 years. Results: Healthy behaviors were found, such as a high percentage of teenagers who brushed their teeth 2 times a day (71.0% in rural and 75.0% in urban area) and the occasional consumption of carbonated drinks by 65.5% of young people from rural area and 55.5% of those from urban area. Unhealthy behaviors were represented by 51.4% of young people from rural area and 43% from urban area who addressed to the dental office only in case of pain, with the last visit being more than one year ago for 58.0% of rural teenagers and 53.5% of urban teenagers. A percentage of 40.9% of urban adolescents declared using mouthwash, while the highest percentage of rural adolescents (42.9%) did not reported using any additional method. An increased daily consumption of cariogenic products several times a day was reported by approximately the same percentage of urban and rural teenagers (49.4% and 42.1%, respectively). In conclusion, the study results indicate differences between the two social areas, with dental visits only in case of pain, dental anxiety, smoking and the prevalence of untreated caries found in the highest percentage among teenagers from rural areas.